Analysis of the gains and losses of ecosystem service value under land use change and zoning in Qiqihar - Zuo, Zhiqian; Yang, Yanzhao; Wang, Ran; Li, Jinxiao; Zhang, Pengtao (Frontiers in Ecology and Evolution, 2023)
Under a background of uncoordinated economic development and the ecological environment, quantifying the ecological effect brought by land resource changes, have become research key and hotspots. To explore land use change and its impact on ecosystem service value (ESV), the land use change analysis method, ecosystem service evaluation model, flow direction analysis model and two-dimensional graph theory clustering method were used to analyze the profit and loss of ESV in Qiqihar in 2010 and 2020 and the division of ecological function areas with counties as units. The results show that: 1) The land use change in Qiqihar city is more obvious, Among them, the area of cultivated land, wetland, construction land and other increases, Woodland, grassland, water area decreased, The changed land area accounts for 30.95% of the total area; 2) The ESV in Qiqihar city increased by 869 million yuan, The sum of the value of cultivated land and wetland exceeded 70.0% of the ESV, is the main source of ESV in Qiqihar city; 3) Not all land-use shifts are conducive to ESV growth. The increase of ESV mainly comes from the flow of cultivated land and grassland to the wetland; Conversion of woodlands, water area, wetlands to other types causes ESV loss, the most loss is the conversion of wetlands to cultivated land; 4) Qiqihar city is divided into the central wetland ecological conservation area, the western characteristic agriculture and dotted wetland ecological function area, and the northeast agricultural ecological environment construction functional area. Three policies were proposed to improve ESV:(1) give play to the radiation role of wetland nature reserves; (2) popularize the black land protection technology model; and (3) prevent and control agricultural non-point source pollution and promote clean agriculture.